Routing in ad-hoc wireless networks - Maung Aung Zeya Thu. (2008)
The objectives of this research are to examine, implement and evaluate the current proposed algorithms on constructing multicast tress for ad hoc networks and to propose a new algorithm, which is computationally efficient and resilient to frequent changes and dynamic nature of wireless networks.